Geoparnus loebli, a new species of terrestrial dryopid from Peninsular Malaysia (Coleoptera: Dryopidae) - Kodada, Ján; Kadubec, Michal; Čiampor, Fedor Jr (Zootaxa, 2013)
Three species have been recognized in the genus Geoparnus Besuchet, 1978, all collected by sifting ground debris from tropical rainforests of Malaysia. The new species Geoparnus loebli sp. nov. is described; morphological similarities to known species G. setifer Besuchet, 1978 and G. rhinoceros Kodada, Jäch, Čiampor Jr & Čiamporová-Zaťovičová, 2007 are discussed. Habitus of adult, male and female genitalia as well as other diagnostic characters are illustrated.